Incorporation of Alternative Fuels and Raw Materials (AFR) to Produce a Sustainable Cement - Benlamoudi, Ali; Kadir, Aeslina Abdul; Khodja, Mohamed (International Journal of Engineering and Technology, 2018)
Throughout the last two decades, tremendous researches have been carried out to investigate the possibility to reduce the cement plants’ costs in terms of raw materials and fuel consumption. Different types of alternative fuels and raw materials (AFR) have been used and proved their efficiencies such as sewage sludge, used tires, crushed aggregates, refuse derived fuel (RDF), red mud, ash and others. Generally, it has been deduced that the possibility to incorporate AFR to produce an acceptable quality of cement is related mainly to its calorific value and its chemical composition. As results, it was reported that incorporation of AFR has reached up to 100% for raw materials substitution and more than 30% for fossil fuel replacement. Nevertheless, the AFR may contain toxic components such as volatile content and heavy metals that need careful attention in its decisive use since it may pose serious problems to the environment and the living things. More parameters may affect the cement production cost including the moisture content of AFR, the burning temperature, the residential time, the accessibility to the AFR, the easy handling and others. The high moisture content of the AFR may increase the total cost of cement production because of the need of a high thermal energy to dry it prior to be incorporated into cement plant. Same thing goes with temperature needed by the AFR to be burned within the kiln. This overview summarizes the studies throughout the last two decades related to cement manufacturing by using AFR based on the main parameters studied by the researchers, the main advantages and the main disadvantages.